Holocene environments of central Iturup Island, southern Kuril archipelago, Russian Far East. Issue 1 (12th June 2017) - Lozhkin, Anatoly; Minyuk, Pavel; Cherepanova, Marina; Anderson, Patricia; Finney, Bruce
Abstract: Two lake records document Holocene changes in sea level, vegetation, and climate on the Okhotsk and Pacific sides of central Iturup Island, southern Kuril Islands. The sediment cores originated within tidal flats that subsequently developed into a marine strait which crosscut the island as sea levels rose during the early Holocene. Brackish lagoons and eventually freshwater lakes formed by ~7100 cal yr BP associated with warmer than present conditions. Past vegetation changes indicate a clear Holocene thermal maximum recorded on the Pacific coast but a less distinct optimum on the western shores (~7200–6100 cal yr BP). A gradual cooling toward modern levels occurred ~6100–3500 cal yr BP. Four prominent layers of coarse sediment found in mid- to late Holocene lake deposits may correspond to intervals of climate cooling/dune formation previously documented in coastal sections. Although chronological limitations question the synchronicity of these events across the south Russian Far East, it seems probable that they have a regional signature. However, the mechanisms responsible for Holocene climatic changes are likely the result of complex interactions of hemispheric-scale atmospheric patterns, marine characteristics, and regional feedbacks rather than simply fluctuations in sea levels as suggested in the current interpretative model.